Efektifitas Peran Komite Sekolah dalam Peningkatan Mutu Sekolah - Firman Firman; Arfin Arfin (Journal of Education and Teaching (JET), 2022)
This study aims to describe the effectiveness of the school committee's role in quality improvement. This study uses a qualitative method, namely to describe the effectiveness of the four roles of the school committee, namely as a giver of consideration, as a controller, as a supporter, and as a mediator. The research subjects were the head of the school committee, the principal, committee members, teachers, parents of students, the community, and school stakeholders. Data were collected through interviews, document studies, and observation. The data analysis technique uses the process of data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data is done through the credibility test of the data. The results of the study found that the role of the school committee was effective in improving quality.